Multidimensional Poverty Indicators in light of ASEAN Integration - Jayvee Faust B. Anga; Jonah Marie S. Enerlas; Kristine June D. Uy; Marjurie Lourince E. Zanoria (Recoletos Multidisciplinary Research Journal, 2015)
This study aimed to explore poverty among ASEAN member nations by introducing a multidimensional poverty index that can be used to determine the relative success of a country in deterring several deprivations that are identified and measured. It utilized multiple factors that can be useful for policy and investment decisions and are intended to complement analyses using financial poverty indicators. Using exploratory data analysis, several indicators were selected to represent the different dimensions of poverty. Said indicators were then subjected to factor analysis which yielded four multidimensional indices namely: General Welfare Index, Governance and Emotional Landscape Index, and Social Climate Index. Singapore, Brunei, and Malaysia ranked 1st, 2nd, and 3rd in all three indices, respectively. In addition, multivariate cluster analysis was also performed. It revealed that Singapore exhibited exceptional performance in all indices, thereby earning it a cluster all to its own. Similarities were observed between Brunei and Malaysia while Thailand, Vietnam, Philippines, and Indonesia were clustered together. Cambodia, Lao PDR, and Myanmar belonged to another cluster, indicating similarities among them. The study concluded that a wide gap exists among ASEAN countries in terms of the various deprivations measured. It also identified several problem areas and strengths of the ASEAN member states. This information can be helpful in making sound judgments especially in the delicate circumstances that surround economic integration.